Game Edukasi Fisika Berbasis Smartphone Android Sebagai Media Pembeajaran Fisika - Wati, Widya; Istiqomah, Heti (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: The purpose of this research and development is to develop mobile game physics based on program construct 2 which is a game designed to stimulate thinking power including increasing concentration and solving problems. This research method is research and development (R and D) based on the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The method of retrieving data in this study is through the results of validation and testing of respondents. The validation results obtained from 5 validators with several aspects of assessment obtained an average of 3.70 with the category